Penggunaan Bokashi Kayambang pada Budidaya Ubi Alabio dengan Pengolahan Lahan - Nurul Istiqomah; Mahdiannoor; Muhammad Muhiddin (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2019)
Alabio yam is one of the alternative food helpers during a famine when rice, sago, and others cannot be harvested, alabio yam can be a healthy food, but farmers do not cultivate alabio yams to the maximum because farmers do not do fertilization and less optimal soil cultivation to improve it there is a need for good fertilization and tillage. This research was conducted in the Banyu Tajun Hulu Village Sungai Pandan District Hulu Sungai Utara District with the title Use of kayambang bokashi on alabio yam cultivation with land management from February to August 2019. using a factorial randomized block design (RBD) with 2 treatment factors, 1 kayambang bokashi and 2 land processing. The first factor is the dose of bokashi kayambang which consists of 5 levels, namely b1 = 5 tons. ha-1 equal with 0.5 kg. plot-1, b2 = 10 tons. ha-1 equal with 1 kg. Plot-1, b3 = 15 tons. ha-1 equal with 1.5 kg. plot-1, b4 = 20 tons. ha-1 is equal to 2 kg. Plot-1, b5 = 20 tons. ha-1 equal with 2.5 kg. plot-1. The second factor consists of 2 levels, namely, t1 = minimum land processing, t2 = maximum land processing. The results showed that the interaction between bokashi kayambang and land management only had a significant effect on the observation of 30 HST. The single factor of bokashi kayambang has a very significant effect on all observational variables. The single factor in land processing only had a significant effect on leaf observation at 20 HST.